Anomalous behaviour of the UV–optical continuum bands in NGC 5548. Issue 4 (30th April 2019) - Goad, M R; Knigge, C; Korista, K T; Cackett, E; Horne, K; Starkey, D A; Peterson, B M; De Rosa, G; Kriss, G A; Edelson, R; Fausnaugh, M
ABSTRACT: During the 2014 HST/Swift and ground-based multiwavelength monitoring campaign of NGC 5548 [active galactic nucleus (AGN) STORM], the UV–optical broad emission lines exhibited anomalous, decorrelated behaviour relative to the far-UV continuum flux variability. Here, we use key diagnostic emission lines (Ly α and He ii ) for this campaign to infer a proxy for the all-important variable driving EUV continuum incident upon broad-line region (BLR) clouds. The inferred driving continuum provides a crucial step towards the recovery of the broad emission-line response functions in this AGN. In particular, the ionizing continuum seen by the BLR was weaker and softer during the anomalous period than during the first third of the campaign, and apparently less variable than exhibited by the far-UV continuum. We also report the first evidence for anomalous behaviour in the longer wavelength (relative to λ1157 Å) continuum bands . This is corroborative evidence that a significant contribution to the variable UV–optical continuum emission arises from a diffuse continuum emanating from the same gas that emits the broad emission lines.